Karakterisasi dan Diferensiasi Sel Punca Mesenkimal Asal Jaringan Adiposa Cokelat Monyet Ekor Panjang (Macaca fascicularis) - Sari, Kartika; Mariya, Silmi; Suparto, Irma H; Dewi, Fitriya Nur Annisa; Permanawati, Permanawati; Darusman, Huda S; Sajuthi, Dondin (Jurnal Veteriner, 2022)
Mesenchymal stem cells (MSCs) from adipose tissue, known as multipotent stem cells, is a promising source of stem cells due to its abundance and it can be easily harvested, one of these cells is brown adipose tissue-derived cells which have gained new interest the field of degenerative disease. The aim of this study was to establish MSCs culture from brown adipose tissue (BAT) of Macaca fascicularis , particularly to characterize and evaluate their differentiation ability. MSCs were isolated from BAT obtained from biopsy of three adult male M. fascicularis on scapular area . MSCs were cultured and Polymerase Chain Reaction technique was used to confirm expression of markers for MSCs. The cells were further differentiated using growth media specific for osteocytes, chondrocytes and adipocytes. The results showed that BAT-derived MSCs had fibroblast-like morphology with spindle shape. Markers for MSCs (CD73, CD90, and CD105) were expressed. Importanty, the cells were able to differentiate into osteocytes, adipocytes and chondrocytes. These results showed that BAT of M. fascicularis can be a source for MSCs; these cells may be used further as in vitro model in the studies of regenerative medicine.